ChemInform Abstract: Site‐Selective Tertiary Alkyl—Fluorine Bond Formation from α‐Bromoamides Using a Copper/CsF Catalyst System. Issue 51 (5th December 2016) - Nishikata, Takashi; Ishida, Syo; Fujimoto, Ryo
Abstract: A copper‐catalyzed site‐selective fluorination of α‐bromoamides possessing multiple reaction sites, such as primary and secondary alkyl—Br bonds, using inexpensive CsF is reported.